Pollination biology and breeding system in five nocturnal species of Oenothera (Onagraceae): reproductive assurance and opportunities for outcrossing - Antoń, Sebastian; Denisow, Bożena (Plant systematics and evolution, 2018)
The capacity to produce seed, both by selfing and outcrossing, or mixed mating strategies, is considered a mechanism for overcoming unpredictable pollinator availability. In the present study, we investigate breeding system, insect visitations and the role of insect visitors in the pollination of five species of Oenothera subsect. Oenothera. Field experiments showed that autonomous selfing occurs at bud stage, prior to the opening of the flower. Control flowers showed similar seed set to hand-pollinated flowers, whereas emasculated flowers and those subject to open pollination set fewer seed. These results are consistent with the hypothesis that the investigated Oenothera exhibit a great capacity for autonomous selfing and that selfing is selected in order to provide reproductive assurance. Although flowers were visited mostly by nocturnal lepidopterans, these insects did not precipitate pollination and are thus considered nectar thieves. Conversely, analysis of pollen loads and behavior during foraging by diurnal insect visitors revealed that honeybees and bumblebees are the probable pollinators. We conclude that production of flowers capable of autonomous selfing at bud stage, followed by anthesis and opportunities for outcrossing, probably improves the invasive potential of these Oenothera in Europe, together with a rapid increase in their populations, even when pollinators are scarce.